Toughening type nylon sheet with low water absorption rate
By coextruding the nylon sheet with A-B-C-B-A structure, the hydrogen bonding and covalent bonding of PVB/lithium silicate composite material and glass fiber are used to reduce the water absorption rate of the nylon sheet and improve toughness, solving the problem of high water absorption rate of nylon materials in the prior art, significantly extending the service life.
Patent Information
- Application Number
- CN202510535253.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-07-18
- Estimated Expiration
- 2045-04-27
AI Technical Summary
The prior art is difficult to achieve extremely low water absorption while maintaining the toughness and wear resistance of nylon materials, and cannot meet the needs of the printing industry.
A nylon sheet with A-B-C-B-A structure is formed by coextrusion technology. PVB/lithium silicate composite and POE modified particles are combined in layer A and B. Mixed glass fibers are added to layer B. The water absorption rate is reduced through hydrogen bonding and covalent bonding. POE modified particles are used in layer C to improve toughness.
The water absorption rate of the prepared nylon sheet is less than 0.5%, the water hardness change is less than 3, the initial hardness is 80-85HD, and the test life of the plastic scraper on the machine increases by 4-5 times.
Smart Images

Figure CN120327059A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nylon materials, and particularly relates to a low water absorption toughened nylon sheet. Background Art
[0002] Nylon materials are currently the most widely used engineering plastics, and the more common ones are single 6 and double 6. Nylon has excellent impact resistance, wear resistance, fatigue resistance, corrosion resistance, low friction coefficient, high strength, strong toughness and other characteristics, so it is widely used in the automotive, textile, medical, sports and other industries. However, the water-absorbing property of nylon materials leads to unstable mechanical and rigid properties, which limits the service life of the materials and cannot be further promoted in many application scenarios. In order to reduce the water absorption rate of nylon materials, each manufacturer uses methods such as adding water-blocking additives (such as montmorillonite, nano-titanium dioxide); blending with low water absorption polymers (such as blending and modifying with polyolefins, polystyrene); surface coating modification (such as coating a hydrophobic coating on the surface of nylon materials, surface modification grafting hydrophobicity, etc.) to improve, so that nylon materials have further development in various industries.
[0003] However, the nylon materials used in the printing industry need to maintain a certain toughness and wear resistance, and also have an extremely low water absorption rate (less than 0.5%), while the traditional modification methods (blending, surface modification) can no longer meet the requirements.
[0004] Based on this, a new type of nylon sheet with low water absorption and simultaneous toughening is now studied. Summary of the Invention
[0005] Object of the Invention: The technical problem to be solved by the present invention is to provide a nylon sheet with an extremely low water absorption rate and excellent toughness at the same time.
[0006] Technical Solution: The low water absorption toughened nylon sheet of the present invention is formed into a sheet with an A-B-C-B-A structure by co-extrusion; wherein,
[0007] The A-layer structure includes nylon material, PVB / lithium silicate composite material and POE modified particles in a mass ratio of 100:(10-15):(3-8);
[0008] The B-layer structure includes nylon material, PVB / lithium silicate composite material and mixed glass fibers in a mass ratio of 100:(5-10):(1-3);
[0009] The C-layer structure includes nylon material and POE modified particles in a mass ratio of 100:(5-10);
[0010] The PVB / lithium silicate composite material includes lithium silicate and PVB in a mass ratio of 1:(0.3-0.8).
[0011] The present invention adopts a co-extrusion method to construct a nylon sheet material with an ABCBA structure, and in the A layer and the B layer material, a PVB / lithium silicate composite material is compounded in the nylon material. The PVB / lithium silicate composite material is prepared by grafting PVB onto the lithium silicate with the help of PVB and lithium silicate, and the water-proof property of the prepared A layer and B layer nylon material is improved based on the self-film-forming property of lithium silicate, and inorganic sheet-like obstacles can be formed in the material to prevent water molecules in the air from penetrating inward through the surface, thereby reducing the water absorption rate of the material; and at the same time, with the help of the hydroxyl group of PVB, And with lithium silicate, it can react with the amide bonds of nylon materials in the extruder to form hydrogen bonds (that is, the hydroxyl groups of PVB react with the amide bonds of nylon materials in the extruder to form hydrogen bonds) or covalent bonds (that is, the silicon-oxygen bonds in lithium silicate may react with the carbonyl groups or amino groups in the amide bonds during the co-extrusion reaction to form silicon-oxygen-carbon bonds (Si-OC) or silicon-nitrogen bonds (Si-N) covalent bonds), occupying most of the amide bonds of the nylon material, inhibiting the reaction of the hydroxyl groups of water molecules in the air with the amide bonds in the nylon material, thereby greatly reducing the water absorption rate of the nylon material and improving the service life of the material.
[0012] In addition, the present invention uses glass fibers of different lengths and sizes by compounding mixed glass fibers in the B-layer structural material to enhance the hardness of the prepared nylon material and improve the mechanical properties; on the other hand, the hydroxyl groups of silicon dioxide, the main component of the glass fibers, can also react with the amide bonds of the nylon material in the extruder to form hydrogen bonds, thereby further inhibiting the reaction of the hydroxyl groups of water molecules in the air with the amide bonds in the nylon material.
[0013] Furthermore, the PVB / lithium silicate composite material used in the present invention is prepared by the following steps: dissolving lithium silicate in distilled water, adding PVB powder, silane coupling agent, cationic surfactant and citric acid, then adding ethanol 3-5 times the mass of the PVB powder, stirring and mixing in a closed manner at a temperature of 80-90° C. for 30-45 minutes, and drying in a vacuum oven to remove moisture to obtain a lithium silicate / PVB composite material.
[0014] Preferably, the silane coupling agent may include γ-aminopropyl triethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, vinyl triethoxysilane or γ-methacryloxypropyl trimethoxysilane, and the amount added is 1-3% of the total mass of PVB and lithium silicate. The cationic surfactant may be hexadecyl trimethyl ammonium bromide or hexadecyl trimethyl ammonium chloride, and the amount added is 0.5-1% of the total mass of PVB and lithium silicate. The amount of citric acid added is 0.1-0.3% of the total mass of PVB and lithium silicate.
[0015] Furthermore, the POE modified particles used in the present invention include a POE-g-MAH modified resin, a phenolic material, and an initiator in a mass ratio of 90:(14-18):(0.5-1).
[0016] The present invention uses a phenolic material to improve the POE-g-MAH modified resin with a toughening effect. The macromolecular free radicals on the POE can graft with the phenolic hydroxyl groups of the phenolic material. In addition, the anhydride of MAH can also undergo an esterification reaction with the phenolic hydroxyl groups, thereby obtaining a mixture ion with strong binding force. And due to the introduction of the phenolic material, while further improving the toughness of the nylon material, the hydroxyl groups of the phenolic material react with the amide bonds in the material, occupying most of the amide bonds in the nylon material, inhibiting the reaction between the hydroxyl groups of water molecules in the air and the amide bonds in the nylon material, thus greatly reducing the water absorption rate of the nylon material and improving the service life of the material.
[0017] Furthermore, among the POE modified particles used in the present invention, the phenolic material includes at least two of phenol, nonylphenol, aralkylphenol, cashew phenol, octylphenol, or bisphenol A. The initiator includes dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, potassium persulfate, or sodium persulfate.
[0018] Furthermore, the mixed glass fibers used in the present invention include glass fibers of 500nm, 10um, and 3um in a mass ratio of (2-3):(2-3):1.
[0019] Furthermore, the POE modified particles used in the present invention are prepared by the following steps: After mixing the POE-g-MAH modified resin, the phenolic material, and the initiator, draw the mixture through water at an extruder speed of 230-250°C and 150-200 rpm, and cut the particles.
[0020] Furthermore, the A layer, B layer, and C layer structural materials of the nylon sheet in the present invention also respectively include an antioxidant accounting for 0.3-0.5% of the total mass. The antioxidant includes 2,6-tert-butyl-4-methylphenol, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide, or pentaerythritol tetrakis[β-(3,5-tert-butyl-4-hydroxyphenyl) propionate].
[0021] Advantageous effects: Compared with the prior art, the significant advantages of the present invention are as follows: The nylon sheet is designed into an A-B-C-B-A structure, and through the optimization and improvement of the compound components in the A layer, B layer, and C layer, layer-by-layer protection is formed. Therefore, the prepared nylon sheet not only has an extremely low water absorption rate (water absorption rate < 0.5%), the change in hardness after soaking in water < 3, but also has excellent toughness, with an initial hardness of 80-85 HD. Based on this nylon sheet, the service life of the plastic scraper prepared and tested on the machine is increased by 4-5 times compared with the existing commercially available plastic scrapers. Description of the Drawings
[0022] Figure 1 This is the product drawing of the nylon sheet prepared in Example 1 of the present invention. Detailed implementation manners
[0023] The technical solution of the present invention will be further described in detail below in conjunction with the embodiments.
[0024] It should be noted that the raw materials used in the present invention can all be purchased commercially. Among them, the POE-g-MAH modified resin is a well-known raw material in the art and can be directly purchased commercially. For example, it can be purchased from Jia Yirong Polymer (Shanghai) Co., Ltd.
[0025] For the sheet having an A-B-C-B-A structure formed by the present invention, a five-layer co-extrusion die well-known in the art is used to construct a composite sheet of the (A-B-C-B-A) structure, that is, different materials are melted and plasticized by three independent extruders and then converged into a die through a distribution block to form a five-layer structure film or sheet. When preparing the POE modified particles and the nylon sheet in the present invention, the extrusion temperature can be 230 - 250°C and the extrusion speed can be 150 - 200 rpm. The preparation process can be realized within this range, and the specific process parameters can be flexibly adjusted in actual production.
[0026] In addition, the mixed glass fibers used in the B-layer structure material of the present invention may include glass fibers of 500 nm, 10 μm, and 3 μm with a mass ratio of (2 - 3):(2 - 3):1. In the following examples, a combination of glass fibers of 500 nm, 10 μm, and 3 μm with a mass ratio of 2:2:1 is used.
[0027] In the following examples of the present invention, the same addition amount of nylon materials is used for different A, B, and C layers. There is no limit on the thickness of each layer, and the total thickness can be maintained between 1.3 - 2.0 mm. For example, the thickness of each layer can be the same to determine the total amount of each layer according to the total thickness requirement.
[0028] Example 1
[0029] The PVB / lithium silicate composite material used in Example 1 was prepared by the following steps: Dissolve lithium silicate in excess distilled water, add PVB powder, γ-aminopropyltriethoxysilane, cetyltrimethylammonium bromide, and citric acid. Subsequently, add ethanol with a mass 4 times that of the PVB powder, and stir and mix tightly at 85 °C for 40 min. Remove moisture through drying in a vacuum oven to obtain the lithium silicate / PVB composite material. Among them, the mass ratio of lithium silicate to PVB is 1:0.5; the addition amount of γ-aminopropyltriethoxysilane accounts for 2% of the total mass of PVB and lithium silicate; the addition amount of cetyltrimethylammonium bromide accounts for 0.8% of the total mass of PVB and lithium silicate; the addition amount of citric acid accounts for 0.2% of the total mass of PVB and lithium silicate.
[0030] The POE modified particles used in Example 1 were prepared by the following steps: Mix POE-g-MAH modified resin with bisphenol A, phenol, and initiator dicumyl peroxide in a ratio of 90:9:7:0.8, and draw and pass through water at an extruder speed of 150 - 200 rpm at 230 - 250 °C, and cut into particles.
[0031] The A-layer structural material of Example 1 includes PA66, PVB / lithium silicate composite material, and POE modified particles with a mass ratio of 100:12:5, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66, PVB / lithium silicate composite material, and POE modified particles.
[0032] The B-layer structural material of Example 1 includes PA66, PVB / lithium silicate composite material, and mixed glass fibers with a mass ratio of 100:8:2, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66, PVB / lithium silicate composite material, and mixed glass fibers.
[0033] The C-layer structural material of Example 1 includes PA66 and POE modified particles with a mass ratio of 100:8, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66 and POE modified particles.
[0034] The nylon sheet of Example 1 was obtained by separately melting and plasticizing the A-layer material, B-layer material, and C-layer material through three independent extruders, and then converging them into a mold at an extrusion temperature of 260 - 285 °C and an extruder speed of 200 - 300 rpm to form a five-layer structured sheet with a thickness of 1.3 - 2.0 mm.
[0035] Example 2
[0036] The PVB / lithium silicate composite material used in this Example 2 was prepared by the following steps: Dissolve lithium silicate in excess water, add PVB powder, γ-aminopropyltriethoxysilane, cetyltrimethylammonium bromide, and citric acid. Subsequently, add ethanol with a mass 4 times that of the PVB powder, and stir and mix hermetically at 85 °C for 40 min. Remove the moisture by drying in a vacuum oven to obtain the lithium silicate / PVB composite material. Among them, the mass ratio of lithium silicate to PVB is 1:0.4; the addition amount of γ-aminopropyltriethoxysilane accounts for 2% of the total mass of PVB and lithium silicate; the addition amount of cetyltrimethylammonium bromide accounts for 0.8% of the total mass of PVB and lithium silicate; the addition amount of citric acid accounts for 0.2% of the total mass of PVB and lithium silicate.
[0037] The POE modified particles used in this Example 2 were prepared by the following steps: Mix the POE-g-MAH modified resin, bisphenol A, phenol, and initiator dicumyl peroxide in a ratio of 90:10:7:0.6, and draw wires at an extruder speed of 150 - 200 rpm at 230 - 250 °C, and obtain particles by underwater pelletizing.
[0038] The A-layer structural material of this Example 2 includes PA66, PVB / lithium silicate composite material, and POE modified particles with a mass ratio of 100:14:6, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66, PVB / lithium silicate composite material, and POE modified particles.
[0039] The B-layer structural material of this Example 2 includes PA66, PVB / lithium silicate composite material, and mixed glass fibers with a mass ratio of 100:6:2, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66, PVB / lithium silicate composite material, and mixed glass fibers.
[0040] The C-layer structural material of this Example 2 includes PA66 and POE modified particles with a mass ratio of 100:6, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66 and POE modified particles.
[0041] The nylon sheet of this Example 2 was obtained by melting and plasticizing the A-layer material, B-layer material, and C-layer material respectively through three independent extruders, and then converging them into a mold at an extrusion temperature of 260 - 285 °C and an extruder speed of 200 - 300 rpm to form a five-layer structure sheet with a thickness of 1.3 - 2.0 mm.
[0042] Example 3
[0043] The PVB / lithium silicate composite material used in this Example 3 is prepared by the following steps: Dissolve lithium silicate in excessive water, add PVB powder, γ-aminopropyltriethoxysilane, cetyltrimethylammonium bromide, and citric acid. Subsequently, add ethanol with a mass 4 times that of the PVB powder, and stir and mix hermetically at 85 °C for 40 min. Remove the moisture through drying in a vacuum oven to obtain the lithium silicate / PVB composite material. Among them, the mass ratio of lithium silicate to PVB is 1:0.6; the addition amount of γ-aminopropyltriethoxysilane accounts for 2% of the total mass of PVB and lithium silicate; the addition amount of cetyltrimethylammonium bromide accounts for 0.8% of the total mass of PVB and lithium silicate; the addition amount of citric acid accounts for 0.2% of the total mass of PVB and lithium silicate.
[0044] The POE modified particles used in this Example 3 are prepared by the following steps: Mix the POE-g-MAH modified resin, bisphenol A, phenol, and the initiator diisopropylbenzene peroxide in a ratio of 90:7:8:0.9, and draw and cut into particles by passing through water under the conditions of an extrusion temperature of 230 - 250 °C and an extrusion machine speed of 150 - 200 rpm.
[0045] The A-layer structural material of this Example 3 includes PA66, PVB / lithium silicate composite material, and POE modified particles with a mass ratio of 100:13:7, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66, PVB / lithium silicate composite material, and POE modified particles.
[0046] The B-layer structural material of this Example 3 includes PA66, PVB / lithium silicate composite material, and mixed glass fibers with a mass ratio of 100:7:2, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66, PVB / lithium silicate composite material, and mixed glass fibers.
[0047] The C-layer structural material of this Example 3 includes PA66 and POE modified particles with a mass ratio of 100:7, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.4% of the total mass of PA66 and POE modified particles.
[0048] The nylon sheet of this Example 3 is obtained by melting and plasticizing the A-layer material, B-layer material, and C-layer material respectively through three independent extruders, and then converging them into a mold under the conditions of an extrusion temperature of 260 - 285 °C and an extrusion machine speed of 200 - 300 rpm to form a five-layer structured sheet with a thickness of 1.3 - 2.0 mm.
[0049] Example 4
[0050] The PVB / lithium silicate composite material used in this Example 4 was prepared by the following steps: Dissolve lithium silicate in excess water, add PVB powder, γ-aminopropyltriethoxysilane, cetyltrimethylammonium bromide, and citric acid, then add ethanol with a mass three times that of the PVB powder, and stir and mix tightly at 80 °C for 45 min, and dry to remove moisture in a vacuum oven to obtain the lithium silicate / PVB composite material. Among them, the mass ratio of lithium silicate to PVB is 1:0.3; the addition amount of γ-aminopropyltriethoxysilane accounts for 1% of the total mass of PVB and lithium silicate; the addition amount of cetyltrimethylammonium bromide accounts for 0.5% of the total mass of PVB and lithium silicate; the addition amount of citric acid accounts for 0.1% of the total mass of PVB and lithium silicate.
[0051] The POE modified particles used in this Example 4 were prepared by the following steps: Mix the POE-g-MAH modified resin, bisphenol A, phenol, and initiator dicumyl peroxide in a ratio of 90:7:7:0.5, and draw and cut into particles under the conditions of an extrusion temperature of 230-250 °C and an extrusion speed of 150-200 rpm.
[0052] The A-layer structural material of this Example 4 includes PA66, PVB / lithium silicate composite material, and POE modified particles with a mass ratio of 100:10:3, and 2,6-tert-butyl-4-methylphenol accounting for 0.3% of the total mass of PA66, PVB / lithium silicate composite material, and POE modified particles.
[0053] The B-layer structural material of this Example 4 includes PA66, PVB / lithium silicate composite material, and mixed glass fibers with a mass ratio of 100:5:1, and 2,6-tert-butyl-4-methylphenol accounting for 0.3% of the total mass of PA66, PVB / lithium silicate composite material, and mixed glass fibers.
[0054] The C-layer structural material of this Example 4 includes PA66 and POE modified particles with a mass ratio of 100:5, and 2,6-tert-butyl-4-methylphenol accounting for 0.3% of the total mass of PA66 and POE modified particles.
[0055] The nylon sheet of this Example 4 was obtained by melting and plasticizing the A-layer material, B-layer material, and C-layer material respectively through three independent extruders, and then converging them into a mold under the conditions of an extrusion temperature of 260-285 °C and an extrusion speed of 200-300 rpm to form a five-layer structured sheet with a thickness of 1.3-2.0 mm.
[0056] Example 5
[0057] The PVB / lithium silicate composite material used in this Example 5 is prepared by the following steps: Dissolve lithium silicate in excess distilled water, add PVB powder, γ-aminopropyltriethoxysilane, cetyltrimethylammonium bromide, and citric acid. Subsequently, add ethanol with a mass 5 times that of the PVB powder, and stir and mix in a closed container at 90 °C for 30 min. Then, dry it in a vacuum oven to remove moisture to obtain the lithium silicate / PVB composite material. Among them, the mass ratio of lithium silicate to PVB is 1:0.8; the addition amount of γ-aminopropyltriethoxysilane accounts for 3% of the total mass of PVB and lithium silicate; the addition amount of cetyltrimethylammonium bromide accounts for 1% of the total mass of PVB and lithium silicate; the addition amount of citric acid accounts for 0.3% of the total mass of PVB and lithium silicate.
[0058] The POE modified particles used in this Example 5 are prepared by the following steps: Mix the POE-g-MAH modified resin, bisphenol A, phenol, and initiator diisopropylbenzene peroxide in a ratio of 90:9:9:1, and extrude and draw the mixture through a water bath and pelletize it at a temperature of 230 - 250 °C and an extruder speed of 150 - 200 rpm to obtain the particles.
[0059] The A-layer structural material of this Example 5 includes PA66, PVB / lithium silicate composite material, and POE modified particles with a mass ratio of 100:15:8, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.5% of the total mass of PA66, PVB / lithium silicate composite material, and POE modified particles.
[0060] The B-layer structural material of this Example 5 includes PA66, PVB / lithium silicate composite material, and mixed glass fibers with a mass ratio of 100:10:3, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.5% of the total mass of PA66, PVB / lithium silicate composite material, and mixed glass fibers.
[0061] The C-layer structural material of this Example 5 includes PA66 and POE modified particles with a mass ratio of 100:10, and 2,6-di-tert-butyl-4-methylphenol accounting for 0.5% of the total mass of PA66 and POE modified particles.
[0062] The nylon sheet of this Example 5 is obtained by separately melting and plasticizing the A-layer material, B-layer material, and C-layer material through three independent extruders, and then converging them into a mold at an extrusion temperature of 260 - 285 °C and an extruder speed of 200 - 300 rpm to form a five-layer sheet with a thickness of 1.3 - 2.0 mm.
[0063] Comparative Example 1
[0064] The basic steps are the same as those in Example 1, except that: in the A-layer structural material, B-layer structural material, and C-layer structure, only PVB is used to replace the PVB / lithium silicate composite material.
[0065] Comparative Example 2
[0066] The basic steps are the same as those of Example 1, except that: in the A-layer structural material, B-layer structural material, and C-layer structure, only POE-g-MAH modified resin is used to replace the POE modified particles.
[0067] Performance detection
[0068] For the nylon sheets prepared in the above Examples 1 to 5 of the present invention, as well as Comparative Example 1 and Comparative Example 2, water absorption tests, changes in hardness after soaking in water, and wear resistance tests were respectively carried out. The obtained results are shown in Table 1 below. Among them, for the water absorption test, the sheet was soaked in distilled water, and the weight and hardness before and after soaking were weighed and measured, and the moisture absorption rate was calculated.
[0069] Table 1 Performance detection of Examples 1 to 5, Comparative Example 1 and Comparative Example 2
[0070]
[0071] Combined with Table 1, it can be seen that the nylon sheets prepared by the present invention are designed into an A-B-C-B-A layer-by-layer protection structure, and through the optimization and improvement of the compound components in the A layer, B layer and C layer, the prepared nylon sheets not only have an extremely low water absorption rate (water absorption rate < 0.5%), a change in hardness after soaking in water < 3, but also have excellent toughness, and the initial hardness is 80-85 HD.
[0072] In addition to the above examples, by using the components and contents defined in the present invention, as well as the specific substances of the components used, the technical effects claimed above in the present invention can be achieved, and thus no further experimental verification will be given one by one.
[0073] For example, the silane coupling agent may also include γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, vinyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane. The cationic surfactant may also be cetyltrimethylammonium chloride. The phenolic materials may at least include two of phenol, nonylphenol, aralkylphenol, cashew phenol, octylphenol or bisphenol A. The initiator may also include benzoyl peroxide, lauroyl peroxide, potassium persulfate or sodium persulfate. The antioxidant may also include bis(3,5-tert-butyl-4-hydroxyphenyl)sulfide or pentaerythritol tetrakis[β-(3,5-tert-butyl-4-hydroxyphenyl)propionate].
Claims
1. A low water absorption toughened nylon sheet, characterized in that, The nylon sheet is formed by co-extrusion to form a sheet with an A-B-C-B-A structure; wherein, The A-layer structure includes nylon material, PVB / lithium silicate composite material and POE modified particles with a mass ratio of 100:(10-15):(3-8); The B-layer structure includes nylon material, PVB / lithium silicate composite material and mixed glass fibers with a mass ratio of 100:(5-10):(1-3); The C-layer structure includes nylon material and POE modified particles with a mass ratio of 100:(5-10); The PVB / lithium silicate composite material includes lithium silicate and PVB with a mass ratio of 1:(0.3-0.8).
2. The low water absorption toughened nylon sheet according to claim 1, characterized in that, The PVB / lithium silicate composite material is prepared by the following steps: dissolving lithium silicate in distilled water, adding PVB powder, silane coupling agent, cationic surfactant and citric acid, then adding ethanol with a mass 3-5 times that of the PVB powder, and stirring and mixing in a closed state at a temperature of 80-90 °C for 30-45 min, and drying to remove moisture in a vacuum oven to obtain the lithium silicate / PVB composite material.
3. The low water absorption toughened nylon sheet according to claim 2, wherein The silane coupling agent includes γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidyletheroxypropyltrimethoxysilane, vinyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane, and the addition amount accounts for 1-3% of the total mass of PVB and lithium silicate.
4. The low water absorption toughened nylon sheet according to claim 2, characterized in that, The cationic surfactant is cetyltrimethylammonium bromide or cetyltrimethylammonium chloride, and its addition amount accounts for 0.5-1% of the total mass of PVB and lithium silicate.
5. The low water absorption toughened nylon sheet according to claim 2, wherein The addition amount of the citric acid accounts for 0.1-0.3% of the total mass of PVB and lithium silicate.
6. The low water absorption toughened nylon sheet according to claim 1, wherein The POE modified particles include POE-g-MAH modified resin, phenolic material and initiator with a mass ratio of 90:(14-18):(0.5-1).
7. The low water absorption toughened nylon sheet according to claim 6, wherein The phenolic material includes at least two of phenol, nonylphenol, aralkylphenol, cashew phenol, octylphenol or bisphenol A; the initiator includes dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, potassium persulfate or sodium persulfate.
8. The low water absorption toughened nylon sheet according to claim 1, characterized in that, The mixed glass fibers include 500 nm, 10 μm, 3 μm glass fibers with a mass ratio of (2-3):(2-3):
1.
9. The low water absorption toughened nylon sheet according to claim 6, wherein The POE modified particles are prepared by the following steps: mixing the POE-g-MAH modified resin, phenolic material and initiator, and then drawing and passing through water at an extruder speed of 230-250 °C and 150-200 rpm, and pelletizing to obtain particles.
10. The low water absorption toughened nylon sheet according to claim 1, characterized in that, The A-layer, B-layer and C-layer structural materials also respectively include an antioxidant accounting for 0.3-0.5% of the total mass of each layer, and the antioxidant includes 2,6-tert-butyl-4-methylphenol, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide or pentaerythritol tetrakis[β-(3,5-tert-butyl-4-hydroxyphenyl) propionate].